2021
DOI: 10.15700/saje.v41ns1a2005
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ beliefs and practices when teaching life sciences using their second language

Abstract: African township schools are characterised by cultural and linguistic diversity, hence, teachers have the dual task of ensuring that learners grasp scientific concepts, while also catering for the diversity in the learners’ backgrounds. The study reported on here was aimed at investigating teachers’ beliefs and practices in teaching life sciences using English, a language that is not their own home language. The study was underpinned by a socio-constructivist perspective, emphasising how one’s personal context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Learners showed excitement at the prospect of being taught science in their home languages, which Prah (2003) p-ISSN: 2184-044X e-ISSN: 2184-1489ISBN: 978-989-35106-3-6 © 2023 pointed out as an important development since being taught in the mother tongue generally creates a more positive learning environment. Previous research also found that the use of English as a language of learning and teaching marginalises some English second language speaking learners (Motloung, Mavuru, & McNaught, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Learners showed excitement at the prospect of being taught science in their home languages, which Prah (2003) p-ISSN: 2184-044X e-ISSN: 2184-1489ISBN: 978-989-35106-3-6 © 2023 pointed out as an important development since being taught in the mother tongue generally creates a more positive learning environment. Previous research also found that the use of English as a language of learning and teaching marginalises some English second language speaking learners (Motloung, Mavuru, & McNaught, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…When they enter the science classroom, the content is delivered in English. The terminology and concepts in science can be difficult to conceptualise and science can essentially be considered as a language on its own (Motloung, Mavuru, & McNaught, 2021). Learners often utter statements such as 'English is not my mother tongue' and malapropism in their written work is noteworthy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The language barrier will be less of an issue as a result, and their engagement and performance in the subject will both increase. Since they will not learn the language, they will only learn concepts of natural science Motloung et al (2021), political commentators like Dr. Somadoda Fikeni, traditionalists like Zolani Mkiva, and historian and cultural analyst Professor Pitika Ntuli, who affirms that learning in the mother tongue should improve learner performance, all support the claims made by these individuals.…”
Section: Conclusion and Recommendationsmentioning
confidence: 93%
“…To achieve understanding, the utterances must be made on https://doi.org/10.36315/2023v1end117 Education and New Developments 2023 shared ground and in a common language (Yore & Treagust, 2006). In a way the use of English as a LoLT, marginalises some English second language speaking learners (Motloung et al, 2021). The authors of the current paper argue that both English language and scientific language create a learning barrier for the learners whose home languages are different from English, the LoLT.Consequently, the current study sought to determine multilingual learners' perceptions of the role of English language and scientific language in their learning of Natural Sciences.…”
Section: Introductionmentioning
confidence: 99%